RANCANG BANGUN ROBOT LINE FOLLOWER PEMINDAH OBJEK WARNA - Dewantoro, Pandu; Riyanto, Indra (MAESTRO, 2019)
In this final project line follower robot is designed to move color objects. Line follower robot that is made can follow the path with a black line color. This system uses Arduino Mega 2560 as a controller, line sensor as a black line detector on a track, ultrasonic sensor as a distance detection box with a robot with a distance of 5cm, and a color sensor as a red, green and blue color detector contained in the box, and a DC motor as Right wheel drive, left wheel, and pulley on the robot. The mission given to the robot is to find the desired color and move it to the place already provided. For this reason, we need controls that can control the robot in making movements in a flat area with a black line so that the robot can follow the black line well. Broadly speaking, the manufacture of color-based Robot Line Follower is designed using several components consisting of Sensors (RGB), Ultrasonic Sensors, Line Sensors, DC Motors, and Arduino. The working principle of the robot is to walk along the black lines in the arena to find the red, green and blue boxes in positions 1, 2 and 3, then move the found boxes to the space provided. In the tests that have been done, the robot can detect the red, green and blue boxes in positions 1, 2 and 3 and then move them to the space provided.